Application of gradient tree boosting regressor for the prediction of scour depth around bridge piers - B. M. Sreedhara (IWA Publishing, 2021)
Scour around bridge piers is a complex phenomenon and it is essential to assess or predict the scour hazard around bridge piers in tandem with completely understanding its mechanism. To date, there is no exact method for the estimation of scour depth. Nowadays, machine learning techniques are being recognized as effective tools for the prediction of scour depth using experimental data. In the present study, gradient tree boosting (GTB) technique was used for the prediction of scour depth around various pier shapes under different streambed conditions. Sediment size, sediment quantity, velocity, and flow time were used as input parameters to predict the scour depth under clear-water and live-bed scour conditions. The scour depth was predicted for different pier shapes such as, circular, rectangular, round-nosed and sharp-nosed shaped. The GTB model predicted scour depth values were compared with that of the group method of data handling (GMDH) technique. The performance of GTB and GMDH models were then evaluated based on statistical indices such as RRMSE, NNSE, WI, MNE, SI, and KGE. The study concludes that the GTB model performance was relatively superior to that of GMDH in the prediction of scour depth around different pier shapes. HIGHLIGHTS An attempt has been made to predict the bridge scour for various pier shapes under different streambed conditions.; Ensemble Machine Learning methods like Gradient Tree Boosting (GTB) and Group Method of Data Handling (GMDH) were used for prediction of bridge scour.; The study concludes that GTB method can be successfully used for predicting bridge scour.;